Resolution of economic dispatch problem of the morocco network using crow search algorithm - Rachid HABACHI; Achraf Touil; Abdellah Boulal; Abdelkabir Charkaoui; Abdelwahed Echchatbi (Institute of Advanced Engineering and Science, 2019)
The economic dispatch problem of power plays a very important role in the exploitation of electro-energy systems to judiciously distribute power generated by all plants. This paper proposes use of Crow Search Algorithm (CSA), for solving the economic dispatch of two electricity networks: a testing system 6 units and the morocco network the crow search algorithm (CSA) is a recently developed metaheuristic search algorithm inspired by the intelligent behavior of crows..The results obtained by CSA are compared with various results obtained in the literature. Simulation results shows that using CSA can lead to finding stable and adequate power generated that can fulfill the need of both the civil and industrial areas.